Disability and Integration: Gambian Experience (Global Journal of Science Frontier Research, 2016)
This study investigated factors that hinder the integration of Gambians with disabilities into mainstream society through focus groups and surveys. Stigma towards those with disabilities was perceived as common and more community education on the medical causes of disabilities is needed. Full integration surfaced as fundamental and to achieve this, more support is needed, including both concrete supplies as well as training.
Keywords: the gambia; persons with disabilities; community-based rehabilitation